Analisis Pengaruh TPT, UMP, Pertumbuhan Ekonomi, IPM Terhadap Jumlah Penduduk Miskin Pulau Jawa - Kevin Dwi Prassetyo; Zainal Arifin (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2022)
The purpose of this study was to determine the effect of the Open Unemployment Rate, Provincial Minimum Wage, Economic Growth and Human Development Index on the Number of Poor Populations partially and simultaneously in Java. This study uses panel data regression analysis. The results of the study show that the Open Unemployment Rate has a positive and significant effect on the number of poor people on the island of Java. The minimum wage has a negative and significant effect on the number of poor people in Java. Economic growth has a positive and insignificant effect on the number of poor people on the island of Java. The human development index has a negative and significant effect on the Number of Poor Populations in Java Island 2012 – 2020